Distribution of Bone Mineral Density in the Ankle Joint: Correlation with Hindfoot Alignment. Issue 4 (November 2022) - Lintz, Francois; Welck, Matthew J.; Buedts, Kristian; Fernando, Céline; Netto, Cesar de Cesar; Bernasconi, Alessio
Category: Ankle; Basic Sciences/Biologics; Hindfoot Introduction/Purpose: Abnormal Hindfoot Alignment (HA) has been correlated with increased complication rates in ankle fusion or replacement. Altered Bone Mineral Density (BMD) due to abnormal stress distribution could be predisposing factor for those unwanted outcomes. The objective of this study was to assess spatial distribution of BMD around the ankle joint in patients with normal or abnormal HA using cone beam Weight Bearing CT. Methods: Retrospective comparative study including 81 ankles allocated into 3 groups based on the Foot Ankle Offset (FAO): 27 normal (0%5%). groups were comparable by age (p=0.967), Body Mass Idex (p=0.669), sex (p=0.820) and side (p=0.708). Semi- automatic segmentation (BoneLogic, Disior) was applied to identify bones. Tibia and talus were digitally compartmented in medial (M) and lateral (L) volumes relative to the median sagittal plane. Mean Hounsfield Unit (HU) value per compartment was used to assess BMD and to calculate the Medial over Lateral HU ratio (M/L-HU). Comparisons among the three groups were performed using one-way ANOVA, Kruskal-Wallis and Chi 2 tests. Results: Mean +- standard deviation HU values in the compartments in normal cases were 495.2+-110 (medial tibia), 495.6+- 108.1 (lateral tibia), 368.9+-80.3 (medial talus), 448.2+-90.6 (lateral talus) and 686.7+-120.4 (fibula). Upon comparison of the mean BMD value for each compartment in the three groups, the difference did not achieve statistical significance. Conversely, the tibia HU-M/L ratio (0.88+-0.14 in valgus cases, 0.99 +- 0.08 in normally-aligned cases and 1.04+-0.08 in varus cases) and the talar HU- M/L ratio (0.68+-0.18 in valgus cases, 0.82+-0.08 in normally-aligned cases and 0.96+-0.20 in varus cases) were significantly different in the three groups (p<0.001). Conclusion: We found that the BMD in distal tibia, fibula and the talus varies with hindfoot alignment. The increased HU medio- lateral ratio in varus cases was consistent with a greater medial bone density in the tibia and talus, while the decreased ratio found in valgus cases suggested a more lateral concentration in both bones. This data supports the role of WBCT in analyzing BMD distribution. This method could be clinically useful in ankle OA to evaluate bone quality for such considerations as surgical indications or implant positioning.